Host plant use of Helicoverpa spp. (Lepidoptera: Noctuidae) in the Brazilian agricultural landscape. Issue 2 (28th September 2020) - Dourado, Patrick M; Pantoja‐Gomez, Laura M; Horikoshi, Renato J; Carvalho, Renato A; Omoto, Celso; Corrêa, Alberto S; Kim, Jae H; Martinelli, Samuel; Head, Graham P
Abstract: BACKGROUND: The Old‐World bollworm, Helicoverpa armigera (Hübner), was recently documented attacking cotton and soybean plants in Brazil; however, restricted basic knowledge on host plant interactions and landscape use in Brazil have limited the effectiveness of control measures. In this study, we evaluated the suitability of different crops commonly cultivated in Brazil as hosts for H. armigera and H. zea, and examined their contribution to the establishment and size of H. armigera and H. zea field populations. We also estimated the proportions of H. armigera and H. zea moths that used cotton, noncotton C3 plants, and C4 plants as hosts in four regions in Brazil through the length of the cropping season. RESULTS: Viability of H. armigera larvae was highest on cotton (46.1%), followed by millet (39.5%), sorghum (31.2%), soybean (24.2%), and maize (21.1%). Noncotton C3 hosts served as the major source of H. armigera moths in all regions evaluated, and C4 hosts were a source of H. armigera mainly in regions where winter maize is typically cultivated. H. armigera moths that used cotton plants as natal hosts were observed during the reproductive stage of the crop mainly in the state of Bahia. Only C4 host plants were a consistent source of H. zea moths, primarily when maize was in the reproductive stage. H. armigera individuals were the main species infesting cotton and soybean fields while H. zea individuals were the main species infesting maize ears. CONCLUSIONS: Regional differences in the host use and population dynamics of H. armigera among the regions evaluated may be attributed to variation in alternative host utilization (crops, noncrops, and weeds) and the possible occurrence of facultative diapause and or migration. Abstract : We evaluated the population dynamic and host suitability for H. armigera and H. zea in Brazil. H. armigera individuals are more abundant and have higher polyphagous behavior than H. zea in the agriculture landscape. © 2020 Society of Chemical Industry